GST와 PtOx 박막의 광학적 성질 및 super-RENS로서의 응용에 관한 연구 - 리학철 (The Graduate School, Ajou University, 2006)
The optical properties of the Ge2Sb2Te5 (GST) and ZnS-SiO2 were determined by using in situ and ex situ ellipsometer. The growth curves of optical recording media were monitored by using in situ ellipsometry in real time, and the optimum growth condition of GST thin film on Si substrate was investigated by varying variables such as Ar gas pressure, DC power and substrate temperature. The complex refractive index spectral of GST and ZnS-SiO2 thin films were also obtained by using ex situ ellipsometry. The super-RENS(super resolution near field structure) based on elliptic bubble formation of PtOx has been proposed by Tominaga et al. In this paper, the optical properties of AgOx and PtOx thin films, whose behavior at high temperatures plays an important role in recording marks and in reading signal of super-RENS, were studied. A series of AgOx and PtOx thin films for various molar oxygen fraction x were prepared by using the reactive magnetron sputtering technique. It is found that AgOx thin film is completely decomposed at 165 °C and its optical properties change irreversibly with temperature. For PtOx thin film, the complex refractive index of PtOx changes monotonically from that of metallic Pt to that of dielectric PtO2 as the molar oxygen fractions increases. It is completely decomposed at 549 °C. In order to understand readout mechanism of PtOx super-RENS with elliptic bubble formation, the complex refractive index of GST was determined at various temperature by in situ ellipsometry. The temperature distribution and the local reflected light intensity were calculated at various Gaussian laser beam positions by utilizing the temperature dependent complex refractive index of GST, and the reflectance was also calculated by integrating the local reflected intensity. The characteristic behavior of super-RENS readout signal was confirmed by calculating the signal to noise ratio(S/N) for several readout powers. Above the threshold readout power, as the center position of Gaussian laser power distribution coincides with the thickest part of GST, it is locally heated and reaches the critical temperature. An abrupt change of the complex refractive index of GST occurs at that position and hence the local reflected intensity at that position increase abruptly. Thus an abrupt increase of the reflectance and amplification of S/N ratio was confirmed for the recording mask smaller than diffraction limit. In summary, the super-RENS effect is attributed to temperature dependent complex refractive index of the GST layer combined with the incident laser power distribution and the thickness variation of the GST layer. The proposed model will contribute to enhance understanding of the super-RENS readout mechanism of elliptic bubble formation and technically improve PtOx based super-RENS data storage.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2006. 2